2015
DOI: 10.1007/s11596-015-1482-6
|View full text |Cite
|
Sign up to set email alerts
|

Prodynorphin gene promoter polymorphism and temporal lobe epilepsy: A meta-analysis

Abstract: Previous studies have reported the association of prodynorphin (PDYN) promoter polymorphism with temporal lobe epilepsy (TLE) susceptibility, but the results remain inconclusive. To further precisely evaluate this association, we performed a meta-analysis. Published studies of TLE and PDYN polymorphism up to February 2015 were identified. Subgroup analysis by TLE subtype was performed. Moreover, sensitivity, heterogeneity, and publication bias were also analyzed. Seven case-control studies were finally include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This result was not replicated in four independent studies of the Caucasian population for TLE [ 134 , 188 , 207 , 208 ]. However, a meta-analysis suggested that the L-allele variant of this promoter polymorphism might contribute as a risk factor for familial-TLE suggesting that further studies are required for acquiring discrete results [ 209 ].…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…This result was not replicated in four independent studies of the Caucasian population for TLE [ 134 , 188 , 207 , 208 ]. However, a meta-analysis suggested that the L-allele variant of this promoter polymorphism might contribute as a risk factor for familial-TLE suggesting that further studies are required for acquiring discrete results [ 209 ].…”
Section: Genetic Studies Of Common Epilepsiesmentioning
confidence: 99%
“…Genetic variants related to ion channels (e.g., SCN1A), calcium signaling (e.g., CALHM1), or neurotransmitter actions (e.g., GABBR1, 5-HTT) have all been linked to common epilepsies, including TLE [ 7 ]. Similarly, SNPs of key neuroregulatory genes were associated with TLE, including known epilepsy-associated genes NRG1 , BDNF , or the PDYN promoter (prodynorphin; [ 159 , 160 , 161 , 162 ]). Furthermore, psychiatric comorbidities increase the risk of acquiring epilepsy, suggesting common dysregulated molecular pathways involved in the pathogenesis of both [ 146 ].…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…The steady-state procedure focuses on the open-water performance and steady-state structural deformation of the composite propeller in a uniform flow field. Shuai Zhang et al [3] used CFD (computational fluid dynamics) method to calculate the open-water performance of 438X (X = 1,2,3) series composite propellers. The pitch changed due to elastic deformation, which mainly affected the hydrodynamic performance.…”
Section: Introductionmentioning
confidence: 99%